Urgency of Employment Protection Regulation for Online Transportation Driver - I Wayan Gde Wiryawan (Sociological Jurisprudence Journal, 2020)
The phenomenon of online application-based transportation services is actually an answer to people's needs for transportation that is easy to get, convenient, fast, and cheap. There are many factors making this online-based application is needed by many people, especially in big cities in Indonesia. Online transportation has become an alternative mode that people want after previously they have to use the conventional modes. Behind the convenience provided, the presence of GO-JEK and Grab has contradictions from various parties. There are no regulations specifically regulating worker protection for the drivers because in Law Number 13 of 2003 concerning Manpower (hereinafter referred to as the Manpower Law) only regulates formal worker. Thus, worker standards in the Manpower Law cannot be applied to online transportation drivers. The urgency to make rules regarding worker protection for online transportation drivers should be considered by the Government. Therefore, it can create legal certainty and justice for the drivers like the formal workers.